Effects of Residual Stress on Creep Crack Initiation and Growth of Cr-Mo-V Steel in Cracked C(T) Specimen. (2015) - Song, X.M.; Wang, G.Z.; Tu, S.-T.; Xuan, F.Z.
Abstract: The effects of residual stress on the creep crack initiation and growth behavior were investigated. It has been shown that the higher compressive residual stress ahead of crack tips delays creep crack initiation and increases creep initiation life, while the higher tensile residual stress promotes creep crack initiation and decreases the initiation life. The residual stress essentially has no effect on creep crack growth rate. In creep life assessments of high temperature components, the effect of residual stress on the creep crack initiation should be mainly considered.